Risk assessment and regulation between the supply and demand of ecological products: A comprehensive framework and case study - Yuhan Huang; Rongrong Ma; Wei Zhou; Yuan Yuan; Jun Ren; Yingui Cao (Ecological Indicators, 2023)
Humans are facing increasing supply–demand risks of ecological products (EPs) due to the uncertainty of the interaction between ecosystems and social systems. To address this issue, a comprehensive framework for risk assessment and regulation is urgently need to identify areas and levels of risk that threaten human well-being. In this study, we constructed a framework for retrospective assessment and optimal regulation of supply–demand risks of EPs, which covers four indicators: the supply–demand index (SDI), the changing trend of SDI, the changing trend of supply, and trade-offs and synergies. Taking Qinghai Province in the northeast of the Qinghai-Tibet Plateau in China as an example, we conducted a case study on five types of EPs: food production, water conservation, carbon sequestration, soil retention, and outdoor recreation. Our results showed that various types of EPs were basically in the state of supply exceeds demand, with significant spatial differences in supply–demand risk levels. Areas with high risk levels were mainly distributed in urban concentrated development areas in the eastern part of the research area, and the spatial matching of supply and demand in these areas often present high supply and high demand. In addition, for the supply–demand risk of different levels of EPs, we proposed intra-regional and cross-regional optimization regulation strategies, combining the spatial matching status of supply and demand of EPs. It can help decision-makers improve the efficiency of the allocation of EPs supply and demand and the scientific nature of policy formulation at a regional scale.